Biogas potential for sustainable transport - A Swedish regional case - Lönnqvist, T.; Sanches-Pereira, Alessandro; Sandberg, T. (ELSEVIER SCI LTD, 2015)
In this study, practical biogas potential has been estimated in order to clarify the role of biogas in policy targets for renewable transport fuels in Sweden. The estimate of the Stockholm County biogas potential is based on a survey directed at key persons at sewage water treatment facilities, as well as official statistics, environmental reports and other sources. The results reveal that the practical biogas potential can meet the vehicle gas demand in Stockholm County by 2020, but that it may cover only 50% of the demand by 2030. The practical potential is estimated to be 604 GWh by 2020 and 689 GWh by 2030. Fossil gas, biogas from neighboring regions, and/or methane from woody biomass would thus be needed to meet the demand by 2030. The survey shows that digestion capacity exists at sewage water treatment facilities and that the availability of resources for biogas generation is low. Public participation is needed to improve food waste segregation and increase resource availability. Food waste can be co-digested with sewage sludge at sewage water treatment facilities. These results can guide the design of renewable transport fuel policies and one conclusion is that policy support should be directed at the supply rather than at the demand side.